Adaptive Synchronization of Complex Dynamical Networks with State Predictor - Yuntao Shi; Bo Liu; Xiao Han (Journal of Applied Mathematics)
This paper addresses the adaptive synchronization of complex dynamical networks with nonlinear dynamics. Based on the Lyapunov method, it is shown that the network can synchronize to the synchronous state by introducing local adaptive strategy to the coupling strengths. Moreover, it is also proved that the convergence speed of complex dynamical networks can be increased via designing a state predictor. Finally, some numerical simulations are worked out to illustrate the analytical results.